Epigenetic changes related to glucose metabolism in type 1 diabetes after BCG vaccinations: A vital role for KDM2B. Issue 11 (8th March 2022) - Dias, Hans F.; Kühtreiber, Willem M.; Nelson, Kacie J.; Ng, Nathan C.; Zheng, Hui; Faustman, Denise L.
Abstract: Background: A recent epigenome-wide association study of genes associated with type 2 diabetics (T2D), used integrative cross-omics analysis to identify 22 abnormally methylated CpG sites associated with insulin and glucose metabolism. Here, in this epigenetic analysis we preliminarily determine whether the same CpG sites identified in T2D also apply to type 1 diabetes (T1D). We then determine whether BCG vaccination could correct the abnormal methylation patterns, considering that the two diseases share metabolic derangements. Methods: T1D (n = 13) and control (n = 8) subjects were studied at baseline and then T1D subjects studied yearly for 3 years after receiving BCG vaccinations in a clinical trial. In this biomarker analysis, methylation patterns were evaluated on CD4+ T-lymphocytes from baseline and yearly blood samples using the human Illumina Methylation EPIC Bead Chip. Methylation analysis combined with mRNA analysis using RNAseq. Results: Broad but not complete overlap was observed between T1D and T2D in CpG sites with abnormal methylation. And in the three-year observation period after BCG vaccinations, the majority of the abnormal methylation sites were corrected in vivo. Genes of particular interest were related to oxidative phosphorylation ( CPT1A, LETM1, ABCG1 ), to the histone lysine demethylase gene ( KDM2B ), and mTOR signaling through the DDIT4 gene. The highlighted CpG sites for both KDM2B and DDIT4 genes were hypomethylated at baseline compared to controls; BCG vaccination corrected the defect by hypermethylation. Conclusions: Glycolysis is regulated by methylation of genes. This study unexpectedly identified both KDM2B and DDIT4 as genes controlling BCG-driven re-methylation of histones, and the activation of the mTOR pathway for facilitated glucose transport respectively. The BCG effect at the gene level was confirmed by reciprocal mRNA changes. The DDIT4 gene with known inhibitory role of mTOR was re-methylated after BCG, a step likely to allow improved glucose transport. BCGs driven methylation of KDM2B 's site should halt augmented histone activity, a step known to allow cytokine activation and increased glycolysis.